Protocol to study adenosine release in the adult mouse hippocampus using a genetically encoded sensor, 2-photon live imaging, and fiber photometry - Coralie Berthoux; Pablo E. Castillo; Kaoutsar Nasrallah (STAR Protocols)
Summary: Genetically encoded fluorescent sensors are powerful tools for tracking real-time neuromodulator dynamics. Here, we present a protocol to measure adenosine release using the G protein-coupled receptor activation-based adenosine (GRABAdo1.0m) sensor in the mouse hippocampus. We describe steps for stereotaxic surgery, including virus injection and optic fiber implantation, ex vivo two-photon live imaging, and in vivo fiber photometry. We then detail histological procedures for experimental validation.For complete details on the use and execution of this protocol, please refer to Nasrallah et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.